Evaluation Of Wind Turbine Potentiality At Windy Sites In Malaysia. - Bawadi, M. A.; Hussin, W. M. Aminuddin Wan; Majid, Taksiah A.; Shmshad, A. (2003)
Wind speed data in Malaysia has been Used, which was recorded hourly from years 1995 t 2002 at three meteorological stations, Mersing, Cameron Highland (Peninsular Malaysia) and Pulau Labuan ( Sabah state). The wind speed distribution and wind power were evaluated to provide spatial mean information of wind energy potential.